The attitudes towards HIV testing among Mall Clinic patients in Botswana - Mashinya, Tawanda (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.